Incidence of Chlamydia trachomatis Infection in Infertile Urban Population - D. Joseph Pushpa Innocent, G. Prathiba, (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Chlamydia trachomatis<span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> emerges as a most common sexually transmitted organism. It affects the young sexually active persons. It has been proved that genital infection with Chlamydia trachomatis markedly enhances the risk of reproductive sequelae in women leading to ectopic pregnancy and infertility. In males, it causes urethritis, prostitis, orchitis and epididymitis. The study was considered to rule out the incidence of Chlamydia trachomatis infection in various age groups of infertile men and women. A total of 446 infertile men and women were included in the study. Blood samples were collected and the IgM and IgG antibodies against Chlamydia trachomatis were studied by ELISA. The results showed Chlamydia trachomatis prevalence rate of 62% in women with a high incidence of infection in the age group of 26-30 years. In the infertile men, the prevalence rate was 37% with a high incidence in the age group of 31-35 years. The overall seroprevalence of Chlamydia trachomatis infection among the 446 infertile men and women tested showed 52% positivity. Thus, there is a need for investigation and treatment of Chlamydia trachomatis infection in infertile population. <span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">----------------------------------------------------------------------------------------------------- <span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Division of Microbiology, Rajah Muthiah Medical College (RMMC), Annamalai University, Annamalai Nagar, Chidambaram, India Cite This Article As: G. Prathiba, D. Joseph Pushpa Innocent. 2010. Incidence of Chlamydia trachomatis Infection in Infertile Urban Population. J. Ecobiotechnol. 2(3): 07-11.